Contribution To The Study Of Flocculation Of Digestate - Heviánková Silvie (GeoScience Engineering, 2015)
The paper deals with the intensification of separating the solid phase of digestate using flocculants only. The separated solid phase should subsequently be used in agriculture for fertilising. Flocculants (polyacrylamides) are difficult to biodegrade. In this respect, they should not deteriorate the properties of the solid phase and the flocculant dose must be as low as possible. The research aimed to identify the optimal cationic flocculant and its application procedure which would enable a dosage that would be both economically and ecologically acceptable. We tested 21 cationic flocculants of different charge density and molecular weight and 1 mixture of two selected flocculants (Sokoflok 53 and Sokoflok 54) with the aim to discover the lowest possible dose of flocculating agent to achieve the effective aggregation of digestate particles. The lowest flocculant doses were obtained using the mixture of flocculants labelled Sokoflok 53 and Sokoflok 54 in 4:1 proportion, both of a low charge density and medium molecular weight, namely 14.54 g/kg of total solids for a digestate from the biogas plant Stonava and namely 11.80 g/kg of total solids for a digestate from the biogas plant Vrahovice. The findings also reveal that flocculation is most effective during two-stage flocculant dosing at different mixing time and intensity.